5th Anniversary Article: Data‐Driven Materials Science: Status, Challenges, and Perspectives (Adv. Sci. 21/2019) - Himanen, Lauri (Adv Sci (Weinh), 2019)
Data‐driven science is heralded as the new paradigm in materials science. Data infrastructures store vast amounts of materials data. Machine learning algorithms systematically extract knowledge from materials data streams to discover new materials for future technologies and the well‐being of society. In article number https://doi.org/10.1002/advs.201900808, Patrick Rinke and co‐worker review the current state of data‐driven materials science. [Image: see text]